1975
DOI: 10.1111/j.1432-1033.1975.tb04083.x
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Hydrogen Exchange in Reactions Catalysed by Cysteine Lyase and Serine Sulphhydrase

Abstract: Serine sulphhydrase from chicken liver and cysteine lyase from chicken-embryo yolk sac catalyse the exchange of alpha-H atoms of the amino acid substrate with 3-H-2O. The degree of labelling of the unreacted substrate approaches a maximum of one atom per mol of amino acid. In the absence of replacing agent there is practically no H-exchange in the substrate. The alpha-H of the accumulating beta-substitution product is completely replaced by the labelled hydrogen of the solvent water, irrespective of the durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…3) are fairly similar to those recently reported by Tolosa et al (25) for serine sulfhydrase and cysteine lyase. With these two fl-replacing lyases, in marked contrast to the a,fl-eliminating or plurifunctional ones (e.g., tryptophanase, y-cystathionase), it was found that isotopic H exchange (1) requires the presence of adequate cosubstrate, (2) mostly is not catalyzed in substrate analogs that do not undergo the complete reaction, (3) is limited to the a-H atom, (4) its rate is of the same order as that of the From these and other properties of the selectively f-replacing lyases, it was inferred that they do not comply to…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…3) are fairly similar to those recently reported by Tolosa et al (25) for serine sulfhydrase and cysteine lyase. With these two fl-replacing lyases, in marked contrast to the a,fl-eliminating or plurifunctional ones (e.g., tryptophanase, y-cystathionase), it was found that isotopic H exchange (1) requires the presence of adequate cosubstrate, (2) mostly is not catalyzed in substrate analogs that do not undergo the complete reaction, (3) is limited to the a-H atom, (4) its rate is of the same order as that of the From these and other properties of the selectively f-replacing lyases, it was inferred that they do not comply to…”
Section: Discussionsupporting
confidence: 79%
“…Evidence reported earlier (8,9,25) demonstrated that some pyridoxal-P-dependent enzymes playing important roles in the metabolism of hydroxy and sulfur amino acids, such as cysteine lyase, serine sulfhydrase, or cystathionine f-synthase, belong to a special subgroup of lyases which catalyze exclu- (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism of free ␤-CNAla synthesis is quite different from that of the ␤-CNAla residue formation reported here: free ␤-CNAla is synthesized by ␤-re-placement of the mercapto group in cysteine by cyanide (25), whereas the ␤-CNAla residue is formed by ␣,␤-elimination of the imidate as shown in Scheme 2.…”
Section: Determination Of the Structure Causing The 73-da Increase-tomentioning
confidence: 86%